Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1971
DOI: 10.1007/bf01963830
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of mitochondria 20 the effects of altered membrane lipid composition on mitochondrial oxidative phosphorylation inSaccharomyces cerevisiae

Abstract: Abstract1. The lipid composition of mitochondria isolated from a fatty acid desaturase mutant of Saccharomyces cerevisiae may be extensively manipulated by growing the organism on defined supplements of unsaturated fatty acid (UFA).2. The fatty acid composition of the mitochondrial lipids closely follows that of the whole ceils from which the mitochondria are isolated. UFA-depleted mitochondria contain normal levels of sterols, neutral lipids and total phospholipids, but have much lower levels of phosphatidyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…The second potential mechanism involves the nature of the fatty acid side chains of the phospholipids of the mitochondrial membrane. Manipulation of yeast mitochondrial membrane fatty acids has been shown to result in changes in the proton permeability and phosphorylating ability (Haslam et al, 1971). We have shown here (Table 3) that there are substantial differences in the membrane fatty acids between lizard and rat mitochondria and suggest that these may be related to the increased proton permeability of the mammalian mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The second potential mechanism involves the nature of the fatty acid side chains of the phospholipids of the mitochondrial membrane. Manipulation of yeast mitochondrial membrane fatty acids has been shown to result in changes in the proton permeability and phosphorylating ability (Haslam et al, 1971). We have shown here (Table 3) that there are substantial differences in the membrane fatty acids between lizard and rat mitochondria and suggest that these may be related to the increased proton permeability of the mammalian mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown in yeast, that membrane lipid composition is crucial for cell function. Studies using fatty acid auxotrophs of Saccharomyces cerevisiae, have demonstrated that mitochondria lose the ability to carry out oxidative phosphorylation when the level of unsaturated fatty acids falls below 20% (Haslam et al 1971(Haslam et al , 1973, a phenomenon directly related to decreased cytochrome content and respiratory competence (Watson et al 1975). Amino acid transport in yeast is also influenced by fatty acyl composition (Mishra and Prasad 1987) and membrane fluidity (Mishra and Prasad 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic factors have been involved in mitochondrial biogenesis: the inhibition of oxidative phosphorylation in mitochondrial myopathies (27); the uncoupling of mitochondria by thyroid hormone (28)(29)(30); the modification of the mitochondrial membrane composition (31); and pharmacological products as Diazepam (32), induce mitochondrial proliferation.…”
Section: Epigenetic Controlmentioning
confidence: 99%